Ethiopian Renaissance or How to Turn Dysfunctional into Functional - Hanna Rubinkowska-Anioł (Ksiegarnia Akademicka Publishing, 2019)
African Renaissance is a term which is used to describe new era in African history and strongly serves propaganda reasons. The aim of the article is to analyse the role of this notion in terms of Ethiopia, i.e. how the term is being employed in Ethiopian politics and propaganda. It is stressed that even though the term itself is a new introduction, the idea of building a strong state on the basis of grand tradition has been used in Ethiopian history on several occasions. Nowadays, the best examples of references to Renaissance by the state’s propaganda are to be found in symbolical meaning of the widely discussed and controversial project of construction the Grand Ethiopian Renaissance Dam on Blue Nile. Other aspects of how the term is being employed can be seen in a propaganda film material produced by the Foreign Ministry of Ethiopia in 2015 with the view to advertise the achievements of the government.